Substantive use of artificial intelligence: The role of individual differences - Michael Klesel; Uwe Messer (Frankfurt University of Applied Sciences, Fachbereich 3: Wirtschaft und Recht, 2024)
Artificial intelligence (AI) is becoming increasingly powerful, enabling users to perform tasks more efficiently and effectively. However, not all users are equally able to take advantage of its capabilities. We draw on previous literature that has introduced the concept of "substantive use" - the reflective consideration of how to use a system's features - to better understand individual differences in the context of AI. We contribute to the current literature in three ways: First, we summarize the literature on technology use and describe its relevance for AI-related research. Second, we review the literature and show that IS has already begun to investigate individual differences to understand the use of AI systems. Third, we propose a theoretical model t hat accounts for the direct and configurational effects of individual differences on substantive use behavior. – – Künstliche Intelligenz (KI) wird immer leistungsfähiger und ermöglicht es den Nutzern, Aufgaben effizienter und effektiver auszuführen. Allerdings sind nicht alle Benutzer gleichermaßen in der Lage, diese Fähigkeiten zu nutzen. Wir stützen uns auf frühere Literatur, die das Konzept "substantive use" eingeführt hat - die Überlegung, wie die Funktionen eines Systems genutzt werden können -, um individuelle Unterschiede im Kontext von KI besser zu verstehen. Wir tragen auf drei Arten zur aktuellen Literatur bei: Erstens fassen wir die Literatur zur Nutzung von Technologie zusammen und beschreiben ihre Relevanz für die KI-bezogene Forschung. Zweitens sehen wir die bestehende Literatur durch und zeigen, dass die Forschung im Bereich Wirtschafsinformatik bereits damit begonnen hat, individuelle Unterschiede zu untersuchen, um die Nutzung von KI-Systemen zu verstehen. Drittens schlagen wir ein theoretisches Modell vor, das die direkten und konfigurativen Auswirkungen individueller Unterschiede auf 'substantive use" berücksichtigt.
urn:nbn:de:bsz:946-opus4-69359
Keywords: 330